2018
DOI: 10.7567/jjap.57.0902b2
|View full text |Cite
|
Sign up to set email alerts
|

Designer defect stabilization of the super tetragonal phase in >70-nm-thick BiFeO3 films on LaAlO3 substrates

Abstract: The stability of the “T-like” (T′) phase in BiFeO3 films grown on LaAlO3(001) is investigated. We show that the T′ phase can be stabilized for thicknesses >70 nm under ultralow incident flux conditions in pulsed laser ablation growth. This low flux results in a low growth rate; thus, the sample is held at high temperatures (>600 °C) for much longer than is typical. Transmission electron microscopy and X-ray diffraction analysis suggest that such growth conditions favor the formation of nanoscale “defect pocket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 46 publications
5
27
0
Order By: Relevance
“…This mixed-phase BFO system is a fertile ground for intriguing physical properties including large piezoelectric responses 34,35 and fieldinduced strains 36 , electrochromic effects 37 , non-zero magnetic moments 38 , electrical conductivity [39][40][41] , interesting mechanical properties 42,43 , and is a suitable system for reducing the polarization retention loss 30 . Herein, we demonstrate that by intentionally introducing designer defects, macroscale strain coherence is maintained throughout the thickness of the film, which leads to the preservation of the T' BFO phase and thus a complete suppression of the mixed-phase structures throughout the film 44,45 . These defects pervade the entire film uniformly and apply a local compressive strain.…”
mentioning
confidence: 95%
“…This mixed-phase BFO system is a fertile ground for intriguing physical properties including large piezoelectric responses 34,35 and fieldinduced strains 36 , electrochromic effects 37 , non-zero magnetic moments 38 , electrical conductivity [39][40][41] , interesting mechanical properties 42,43 , and is a suitable system for reducing the polarization retention loss 30 . Herein, we demonstrate that by intentionally introducing designer defects, macroscale strain coherence is maintained throughout the thickness of the film, which leads to the preservation of the T' BFO phase and thus a complete suppression of the mixed-phase structures throughout the film 44,45 . These defects pervade the entire film uniformly and apply a local compressive strain.…”
mentioning
confidence: 95%
“…This effect is ascribed to the presence of a strain-stabilizing Bi 2 O 3 phase. 35,40 More specifically, it has recently been found that fine tuning of growth conditions can favour the formation of "stacking fault" like nanoregions in our T films: these regions appear to help maintain the strain required for T BFO up to larger thicknesses. To determine the structural symmetry, XRD RSMs around the (103) and (113) reflections [Figs.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…The results presented here may suggest that cobalt doping is a possible route to suppress the presence of the mixed phase, i.e., the sustaining of pure T phase for relatively large film thicknesses, and is in agreement with recent studies. 34,35 It is probable that the cobalt doping alone is not responsible for the suppression of the mixed-phase regions, as growth conditions can also be fine-tuned to favour nominally pure T phase films. 35,44 Detailed ferroelectric switching measurements find domain dynamics similar to typical R-like BFO films, while conductive AFM mapping evidences strong conductivity at the domain walls between polarization variants, opening up encouraging possibilities for domain wall-based nanoelectronics using T BFO.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
See 1 more Smart Citation
“…Three growth chambers were used, the respective growth conditions of which can be found in Refs. [ 47,68,69 ] .…”
Section: Methodsmentioning
confidence: 99%